2005
DOI: 10.3997/1873-0604.2005022
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance sounding (MRS) and resistivity characterisation of a mountain hard rock aquifer: the Ringelbach Catchment, Vosges Massif, France

Abstract: International audienceThe Ringelbach catchment, which has been studied since 1975, is highly representative of the crystalline Vosges massif, where the water supply is mainly derived from small aquifers in heterogeneous superficial formations and in the weathered and fissured bedrock. Vertical electrical soundings (VES), resistivity imaging profiles and magnetic resonance soundings (MRS) were applied inorder to investigate the 3D structure and estimate the hydrodynamic characteristics of the subsurface, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
4
18
0
1
Order By: Relevance
“…Many recent and past studies have shown the beneficial usage of surface nuclear magnetic resonance (NMR) for various hydrogeological issues, such as characterization of aquifers in sedimentary (Legchenko et al, 2004;Mohnke and Yaramanci, 2008;Vouillamoz et al, 2008) and fractured rocks (Baltassat et al, 2005;Vouillamoz et al, 2005), in karst (Vouillamoz et al, 2003) and thermokarst environments (Parsekian et al, 2013), identification and characterization of freshwater resources within saltwater environments (Guenther and Müller-Petke, 2012;Vouillamoz et al, 2012;Siemon et al, 2015), melting glaciers (Lehmann-Horn et al, 2012;Legchenko et al, 2014), or arctic sea ice thickness (Nuber et al, 2013). Moreover, the ongoing technical and methodological improvement of the surface NMR method opens new and expands existing application fields.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent and past studies have shown the beneficial usage of surface nuclear magnetic resonance (NMR) for various hydrogeological issues, such as characterization of aquifers in sedimentary (Legchenko et al, 2004;Mohnke and Yaramanci, 2008;Vouillamoz et al, 2008) and fractured rocks (Baltassat et al, 2005;Vouillamoz et al, 2005), in karst (Vouillamoz et al, 2003) and thermokarst environments (Parsekian et al, 2013), identification and characterization of freshwater resources within saltwater environments (Guenther and Müller-Petke, 2012;Vouillamoz et al, 2012;Siemon et al, 2015), melting glaciers (Lehmann-Horn et al, 2012;Legchenko et al, 2014), or arctic sea ice thickness (Nuber et al, 2013). Moreover, the ongoing technical and methodological improvement of the surface NMR method opens new and expands existing application fields.…”
Section: Introductionmentioning
confidence: 99%
“…Some comprehensive Improvements in Inversion of Magnetic Resonance Exploration-Water Content, Decay Time, and Resistivity 593 resumes were given in four special issues following the International Workshops on MRS Plata et al, 2007;Yaramanci and Legchenko, 2005;Valla and Yaramanci, 2002). Extensive surveys and testing have been conducted in different geological and field conditions, particularly in sandy aquifers but also in clay-rich formations as well as in fractured hard rock, at special test sites, and under low earth field conditions (Vouillamoz et al, 2007(Vouillamoz et al, , 2006(Vouillamoz et al, , 2005(Vouillamoz et al, , 2002Meyer et al, 2006;Baltassat et al, 2005;Lange et al, 2005;Dippell and Golden, 2003;Meju et al, 2002;Plata and Rubio, 2002;Supper et al, 2002;Yaramanci et al 2002Yaramanci et al , 1999Beauce et al, 1996;Legchenko et al, 1995;Goldman et al, 1994;Lieblich et al, 1994;Schirov et al, 1991). Meanwhile, the technique has had an increasing impact on hydrogeology as a powerful tool for aquifer characterization Roy, 2007, 2004;Vouillamoz et al, 2007Vouillamoz et al, , 2006Lachassagne et al, 2005;Legchenko et al, 2004;Roy and Lubczynski, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Both MRS equipment and its interpretation software have been well tested and proved their reliability in areas where the electrical conductivity of the subsurface is relatively low and does not cause significant phase shifts in the MRS signal (Schirov et al, 1991;Gev et al, 1996;Yaramanci et al, 1999, Wyns et al, 2004Baltassat et al, 2005;Vouillamoz et al, 2005). However, MRS can be applied not only for studying fresh-water aquifers, but also in areas where salt-water intrusion renders the subsurface electrically conductive.…”
Section: Introductionmentioning
confidence: 99%